2022
DOI: 10.3389/fcvm.2022.982969
|View full text |Cite
|
Sign up to set email alerts
|

Association between albumin infusion and septic patients with coronary heart disease: A retrospective study based on medical information mart for intensive care III database

Abstract: Coronary heart disease (CHD) is a common comorbidity in intensive care unit (ICU) patients, particularly in the elderly. This particular population may have worse conditions during sepsis, and it presents an overwhelming challenge for clinical practice. Previous studies suggested that patients with CHD have an increased risk of cardiovascular events, and low albumin concentration worsens the prognosis of patients with stable CHD. Hypoalbuminemia in patients with sepsis is common due to nutritional disorders, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…The most impactful parameters contributing to predicted mortality risk in sepsis patients were Age, AST, invasive ventilation treatment, and BUN. NLR and serum albumin were also highly predictive of in-hospital mortality in ICU sepsis patients, consistent with previous research [ 56 , 57 ]. Interestingly, some inflammatory biomarkers, such as NHR and MHR, critically impacted hospital mortality of sepsis patients in the XGBoost model.…”
Section: Discussionsupporting
confidence: 91%
“…The most impactful parameters contributing to predicted mortality risk in sepsis patients were Age, AST, invasive ventilation treatment, and BUN. NLR and serum albumin were also highly predictive of in-hospital mortality in ICU sepsis patients, consistent with previous research [ 56 , 57 ]. Interestingly, some inflammatory biomarkers, such as NHR and MHR, critically impacted hospital mortality of sepsis patients in the XGBoost model.…”
Section: Discussionsupporting
confidence: 91%
“…The most impactful input parameters contributing to predicted mortality risk in sepsis patients were age, AST, invasive ventilation treatment, and heart rate. Blood urea nitrogen and serum albumin were also highly predictive of in-hospital mortality in ICU sepsis patients, consistent with previous research 33,34 . Interestingly, some novel in ammatory biomarkers critically impacted hospital mortality of sepsis patients in the XGBoost model.…”
Section: Discussionsupporting
confidence: 90%
“…PE and DVT are collectively referred to as VTE, affecting approximately 10 million people worldwide [20]. Epidemiological evidence has suggested that low serum albumin levels are associated with the occurrence of many cardiovascular diseases, ranging from ischemic heart disease, heart failure, atrial brillation, stroke, and venous thromboembolism itself [21]. Multiple observational studies have revealed that serum albumin levels are correlated negatively with VTE [22][23][24].…”
Section: Discussionmentioning
confidence: 99%